Inflammasomes in neurodegenerative diseases - Qianchen Wang; Songwei Yang; Xuan Zhang; Shanshan Zhang; Liping Chen; Wanxue Wang; Naihong Chen; Jiaqing Yan (Translational Neurodegeneration)
Abstract Inflammasomes represent a crucial component of the innate immune system, which respond to threats by recognizing different molecules. These are known as pathogen-associated molecular patterns (PAMPs) or host-derived damage-associated molecular patterns (DAMPs). In neurodegenerative diseases and neuroinflammation, the accumulation of misfolded proteins, such as beta-amyloid and alpha-synuclein, can lead to inflammasome activation, resulting in the release of interleukin (IL)-1β and IL-18. This activation also induces pyroptosis, the release of inflammatory mediators, and exacerbates neuroinflammation. Increasing evidence suggests that inflammasomes play a pivotal role in neurodegenerative diseases. Therefore, elucidating and investigating the activation and regulation of inflammasomes in these diseases is of paramount importance. This review is primarily focused on evidence indicating that inflammasomes are activated through the canonical pathway in these diseases. Inflammasomes as potential targets for treating neurodegenerative diseases are also discussed.